Black cumin seed oil increase leucocyte and CD4Thelper number in sprague-dawley rats induced with dimethylbenzanthracene - Titiek Hidayati; Akrom Akrom; Indrayanti Indrayanti; Sagiran Sagiran (Intelektual Pustaka Media Utama, 2019)
Cigarette smoke contains 7, 12 dimethylbenzanthracene (DMBA). Metabolic of DMBA is immunosuppressive. Black cumin seed oil (BCSO) is an immunomodulation. The aim of this study was to determine the effect of BCSO on leukocyte, CD4Th and CD4CD25Treg in Sprague-Dawley (SD) mice induced with DMBA. The 96 SD rats were divided into 8 groups of 12. Group I received aquabidest and standard feeding. Groups II, III and IV received BCSO (an equivalent of 6.8, 68 and 136 mg/kg BW / day thymoquinone, respectively). Group V received thymoquinone (50 mg / kg BW / day) and group VI received tamoxifen (60 mg / kg BW). Group VII (DMBA) was induced with DMBA (10x20mg / kg BW for 5 weeks). Group VIII received standard feeding and corn oil treatment. In the third week, all groups began to be induced with DMBA (20 mg/kg BW twice per week for five weeks). Data collection of leukocytes, CD4Th and CD4CD25Treg was performed at week 27th. The mean difference of CD4Th and CD4CD25Treg counts between groups was calculated with one way ANOVA. Results: The administration of BCSO, thymoquinone, and tamoxifen had increased leukocytes and CD4 Th cell count. The CD4Th cell count of the treatment groups was higher than that of the DMBA group (p <0.05). BCSO equivalent doses of 6.8 and 68 mg/kg BW / day thymoquinone showed immunoprotective effects. Conclusion: It can be concluded that the BCSO administration at doses of 6.8 and 68 mg/kg BW / day shows immunoprotective effects due to DMBA induction.